MEMS Varifocal Optical Elements for Focus Control - Chen Liu; Tong Wang; Xin Wang; Manpeng Chang; Yu Jian; Weimin Wang (Micromachines)
As microelectronic devices become more prevalent daily, miniaturization is emerging as a key trend, particularly in optical systems. Optical systems with volume scanning and imaging capabilities heavily rely on focus control. The traditional focus tuning method restricts the miniaturization of optical systems due to its complex structure and large volume. The recent rapid development of MEMS varifocal optical elements has provided sufficient opportunities for miniaturized optical systems. Here, we review the literature on MEMS varifocal optical elements over the past two decades. Based on light control mechanisms, MEMS varifocal optical elements are divided into three categories: reflective varifocal mirrors, varifocal microlenses, and phased varifocal mirrors. A novel indicator is introduced to evaluate and compare the performance of MEMS varifocal optical elements. A wide range of applications is also discussed. This review can serve as a reference for relevant researchers and engineers.